Propagação in vitro e aclimatização de espécies medicinais: Alpinia zerumbet (Pers.) B. L. Burtt. & R. M. Sm. (Zingiberaceae) e Solidago chilensis Meyen (Asteraceae) - Rodrigues, Ana Carolina da Cunha (2016)
(In vitro propagation and acclimatization of medicinal species: Alpinia zerumbet (Pers.) B.L.Burtt&R.M.Sm. (Zingiberaceae) and Solidago chilensis Meyen (Asteraceae). Alpinia zerumbet and Solidago chilensis are known for their ornamental and medicinal values. There are few reports in the literature on micropropagation of Alpinia zerumbet and none about Solidago chilensis, which demonstrates the need for studies. This work aimed to study in vitro propagation of the species, involving micropropagation and developing protocols for organogenesis. For in vitro establishment were tested different types of explants, disinfestation methods and antioxidants. For multiplication, these explants were tested with plant growth regulators naftalen acetic acid and benzilaminopurin isolated and combined, and dichlorophenoxyacetic acid and kinetin, isolated and combined. It was made anatomical characterization of callus formation. For acclimatization, after pre-acclimatization, the seedlings were transferred to plastic cups containing sterilized substrate, capped with plastic bottles and taken to a greenhouse with 50% shading, where the bottle caps were unscrewed slowly. The results showed success in establishing in vitro of A. zerumbet crucial step to start large-scale cultivation. Against contamination, the most effective treatment was 4ml PPM/L (Plant Preservative Mixture), controlling 100% of pathogens. As an antioxidant, ascorbic acid (2%) was the most efficient. There was budding A. zerumbet derivatives bud explants. There was no decline in the propagation rate during in vitro subcultures, however growth is very slow. S. chilensis, explants nodal segments showed a higher rate of multiplication. There was no decline in the spread rate over four subcultures in vitro and the seedlings had a high survival rate in the acclimatization phase.